Work Motivation and Compensation on Employee Performance - Amindrawati, Tri; Bodroastuti, Tri; Ginanjar, Retno (Faculty of Psychology, Universitas Semarang, 2025)
This study aims to analyze the effect of work motivation and compensation on employee performance at Percetakan Sewelas Triwulan. The research employs a quantitative approach with an associative design, involving 32 employees selected through a saturation sampling method. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that work motivation has a significant positive effect on employee performance, with a regression coefficient of 0.65 (p < 0.05). Additionally, compensation has a significant influence on employee performance, with a regression coefficient of 0.58 (p < 0.05). Simultaneously, both motivation and compensation have a significant impact on employee performance, with an F-value of 8.45 (p < 0.05). The implications of this study underscore the importance of management enhancing work motivation through non-financial rewards and ensuring fairness in compensation, thereby creating a productive work environment that supports optimal employee performance.